Hibernoma. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2004)
Hibernoma is a usually benign tumor, although a malignant case has been reported (1), deriving from the brown fat (4, 7). The latter is a specialized form of fat tissue, prominent in hibernating animals (3), probably aimed at producing heat. Two symmetrical masses of brown fat are located on either side of the midline between the scapulae. From this site it may extend towards both the cervical and abdominal region. Hibernoma is a rare tumor, prevailing in the fourth decade, at an average age of 33, although some exceptional cases were reported in children. The tumor is slightly more frequent in females (2, 4, 5). The clinical diagnosis is difficult and can be suspected in presence of a warm, brownish tumor. Both the color and the increased temperature are due to its rich vascularization (6). When these data lack, the histological examination is diriment, showing large cells with a small nucleus and multivacuolated cytoplasm.